2011
DOI: 10.1068/p6774
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Familiarity on Face Adaptation

Abstract: Face aftereffects can provide information on how faces are stored by the human visual system (eg Leopold et al, 2001 Nature Neuroscience 4 89 – 94), but few studies have used robustly represented (highly familiar) faces. In this study we investigated the influence of facial familiarity on adaptation effects. Participants were adapted to a series of distorted faces (their own face, a famous face, or an unfamiliar face). In experiment 1, figural aftereffects were significantly smaller when participants were adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…A number of subsequent studies have demonstrated robust adaptation aftereffects for faces, with manipulations of face shape using different forms of distortion (Rhodes et al, 2003; Carbon and Leder, 2005; Carbon et al, 2007; Jeffery et al, 2007; Carbon and Ditye, 2011; Laurence and Hole, 2011) or through the creation of anti-faces which manipulate aspects of facial shape that are crucial to identification (Leopold et al, 2001; Anderson and Wilson, 2005; Fang et al, 2007). These studies suggest that faces are coded with respect to a prototypical or “average face” and show that sensitivity changes with adaptation, so that perceptual judgments are made with respect to a shifted norm.…”
Section: Introductionmentioning
confidence: 99%
“…A number of subsequent studies have demonstrated robust adaptation aftereffects for faces, with manipulations of face shape using different forms of distortion (Rhodes et al, 2003; Carbon and Leder, 2005; Carbon et al, 2007; Jeffery et al, 2007; Carbon and Ditye, 2011; Laurence and Hole, 2011) or through the creation of anti-faces which manipulate aspects of facial shape that are crucial to identification (Leopold et al, 2001; Anderson and Wilson, 2005; Fang et al, 2007). These studies suggest that faces are coded with respect to a prototypical or “average face” and show that sensitivity changes with adaptation, so that perceptual judgments are made with respect to a shifted norm.…”
Section: Introductionmentioning
confidence: 99%
“…Using adaptation to distorted versions of the participant's own face, a famous face, or an unfamiliar face, smaller adaptation effects were observed when participants judged their own face than when they looked at other face types (Laurence & Hole, 2011). This finding suggests that greater experience/familiarity with specific faces may create a robust representation that is more difficult to alter via adaptation.…”
mentioning
confidence: 66%
“…Adaptation effects have been shown to be smaller when judging one's own face rather than famous or unfamiliar faces (Laurence & Hole, 2011), suggesting that greater experience results in more robust representations that are less prone to adaptation. Our study provided an important opportunity to examine the influence of experience on adaptation effects using different classes of faces.…”
Section: Discussionmentioning
confidence: 99%
“…a very familiar face) had been used as the adaptor, a smaller aftereffect has been found relative to when the adaptor was a familiar or an unfamiliar face. Laurence and Hole (2011) have interpreted this result as indicating that the processing of the self-face requires a smaller amount of attentional resource and, thus, it produces a smaller level of 'neural fatigue' relative to other kinds of faces, which in turn may explain the reduced aftereffect. Further studies have shown no effect of familiarity on the magnitude of the aftereffect.…”
Section: Familiarity and Face Adaptationmentioning
confidence: 99%
“…In order to manipulate familiarity, several studies have used images of famous people (Carbon & Ditye, 2011;Hills & Lewis, 2012;Walther et al, 2013), whereas in other studies participants had been trained with face stimuli (Jiang, Blanz, & O'Toole, 2007Ryu & Chaudhuri, 2006). Only a few studies have examined the effects of adaptation by using personally familiar faces (Rooney et al, 2012;Walton & Hills, 2012), or the participant's own face (Laurence & Hole, 2011;Rooney et al, 2012).…”
Section: Familiarity and Face Adaptationmentioning
confidence: 99%